Alamat ni China Doll - Diaz, Lav; Salvador, Phillip; Montano, Cesar; Panganiban, Angelica; Alix, Adolfo Jr.; Cinema One Originals (Firm). ([Pace of production not identified] Cinema One Originals, 2013)
Helen lives with her grandmother in an idyllic island down South. At 27, she is about to graduate from high school and start a new life. Things take a drastic turn when journalist Perry Nanali's article on the truth about "China Doll" is exposed. Now, she is haunted by her past that she tried to forget.--anonymous
Summary taken from https://www.imdb.com/title/tt3307314/plotsummary?ref_=tt_ov_pl.
Produced by Ronald Arguelles; music by Lav Diaz; cinematography by Albert Banzon.
Phillip Salvador, Cesar Montano, Angelica Panganiban.
DVD
In Tagalog.
Keywords: Drama